2012
DOI: 10.1186/1472-6831-12-59
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors related to dental caries among pre-school children of Saddar town, Karachi, Pakistan: a cross-sectional study

Abstract: BackgroundDental caries is highly prevalent and a significant public health problem among children throughout the world. Epidemiological data regarding prevalence of dental caries amongst Pakistani pre-school children is very limited. The objective of this study is to determine the frequency of dental caries among pre-school children of Saddar Town, Karachi, Pakistan and the factors related to caries.MethodsA cross-sectional study of 1000 preschool children was conducted in Saddar town, Karachi. Two-stage clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 21 publications
6
54
1
3
Order By: Relevance
“…In a study from sadder town Karachi, Pakistan it is 51 % in 2012. In this study, bad oral hygiene and tooth brushing habit was studied [18]. Another study from Karachi shows that ECC rate is 29.1% only, in this study socioeconomic aspect of ECC is discussed and reported that there was an inverse relation between dental caries and family income [13].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a study from sadder town Karachi, Pakistan it is 51 % in 2012. In this study, bad oral hygiene and tooth brushing habit was studied [18]. Another study from Karachi shows that ECC rate is 29.1% only, in this study socioeconomic aspect of ECC is discussed and reported that there was an inverse relation between dental caries and family income [13].…”
Section: Discussionmentioning
confidence: 93%
“…Available data on dental caries reveal that Pakistan has been classified as a low caries country, on the positive side 50% of the children between the ages of 12-15 years are caries free and on the negative side 97% of all carious lesions remained untreated [13,19]. In Karachi (city of Pakistan) ECC prevalence is 51 percent in the year of 2002 as well as in 2012 [18] Prevalence of caries is 60.90% in Lahore [20]. Peshawar is high incidence of ECC in 2015 it is 88.6% which is very high as compared with others [19].…”
Section: Introductionmentioning
confidence: 99%
“…The descriptive statistics of the values of the dmft by tooth surfaces in children, with primary dentition varies in the interval 6,60±3,13in which the minimal value is 2 and the maximum value is 16. The values of the components of the dmft index according to teeth surfaces, for dental caries, vary in the interval 4,63±2,79, in which the maximum value is 12 carious surfaces opposed to the teeth with dental fillings, according to surfaces, which had less and vary in the interval 1,63±2,36, with a maximum of 9 surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries is a biofilm-mediated, sugar-driven, multifactorial, dynamic disease that results in the phasic demineralization and remineralization of dental hard tissues [1] population of several countries is suffering from this problem, children and adults both are found at risk with this disease, a study was conducted in Saudi Arabia among school going children reports 68.9% children were getting effected with this problem [2], another study form Bangalore reports 65.7% prevalence among school going children aged 3-5 years old [3], one more study from India gives 36.5% prevalence of dental caries [4], in Pakistan it was found 51% [5].…”
Section: Introductionmentioning
confidence: 99%